The freight system in Mexico City. Factors to consider in the analysis of freight transportation and freight mobility - Martínez Perdomo, Florián Rosa (Universidad del Rosario, 2010)
The article presents displays an analysis of the system of transport of load in the City of Mexico, from the systemic point of view considering economic, political, technical and social the variables that allow including understand the problematic one that at the moment faces in the mobility of merchandise in the City. It is a reflection of multidisciplinary character based on the qualitative method to explain and to include/understand the present situation of the transport of load in Mexico, within the context of the economic globalization to identify the deep nature of the dynamic structure of the transport of load in the City and the new form conceptualize to the transport of merchandise. One studies the behavior of the flows and infrastructure, of the road networks, the urban characteristics, the legal instruments in the policies of the transport, the problematic one of the load transport, as well as mobility and the different problems that the sector in relation to the city faces. The primary target of present article is to enunciate the reasons for which a system of articulated transport does not exist and the use of the load motor transport is privileged. Finally, according to the diverse analyzed variables one settles down in the conclusions that the analysis and the planning of the transports must be multi and interdisciplinary by nature with an integral vision to establish a balance between the transport ways.